Between Covenant and Contract: Islamic Marriage Law from the Perspective of Matthew 19:4–6 - P. Limiyano, Sem Yogie; Tamba, Damaianti; Silvia, Priskila; Suhartini, Titin; Fidelia, Catherine (Asian Journal of Philosophy and Religion, 2025)
There are some similarities in views on marriage between Islam and Christianity, there are also several striking theological differences between the two religions. Some of the most striking differences concern the laws of marriage and divorce. The research was conducted using a descriptive method with a qualitative approach. Literature review was conducted on various academic sources, including books and journals discussing marriage in Islam and Christianity, as well as expositions of the text of Matthew 19:4-6. The results of the study indicate that the most striking difference between the theological views of Islam and Christianity is that the marriage bond is dissolvable in Islam but indissolvable in Christianity. Furthermore, Islam adheres to the ideal monogamy with the possibility of polygamy, while Christianity adheres to absolute monogamy.